2022
DOI: 10.1038/s41598-022-18376-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of online parietal transcranial electric stimulation on associative memory: a direct comparison between tDCS, theta tACS, and theta-oscillatory tDCS

Abstract: Associative memory (AM) is the ability to remember and retrieve multiple items bound together. Previous studies aiming to modulate AM by various transcranial electric stimulation (tES) techniques were inconclusive, although overall suggestive that tES could be a tool for AM enhancement. However, evidence from a direct comparison between different tES techniques is lacking. Here, in a sham-controlled cross-over experiment, we comparatively assessed the effects of three types of tES—anodal tDCS, theta-band trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Specifically, 18 out of 29 studies found positive tES effects on AM, 7 studies presented evidence of tES decreasing AM performance, while 4 studies reported null effects on all AM outcomes. There is no apparent relationship between the AM effects and the type of tES protocol applied, as positive effects were reported following anodal tDCS [ 32 , 33 , 44 , 47 , 49 , 52 , 53 , 57 ], tACS [ 58 , 59 ], otDCS [ 52 , 59 ], HD-tDCS [ 54 ], HD-tACS [ 48 ] and even cathodal tDCS [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, 18 out of 29 studies found positive tES effects on AM, 7 studies presented evidence of tES decreasing AM performance, while 4 studies reported null effects on all AM outcomes. There is no apparent relationship between the AM effects and the type of tES protocol applied, as positive effects were reported following anodal tDCS [ 32 , 33 , 44 , 47 , 49 , 52 , 53 , 57 ], tACS [ 58 , 59 ], otDCS [ 52 , 59 ], HD-tDCS [ 54 ], HD-tACS [ 48 ] and even cathodal tDCS [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…When PPC was targeted, the effects on AM were predominantly positive [ 34 , 39 , 44 , 47 , 49 , 52 , 59 ], with only three studies showing negative [ 35 , 55 ] or null effects [ 31 ]. The effects of frontal stimulation were much more mixed—some experiments showed AM improvement [ 32 , 33 , 37 , 45 , 48 , 50 , 53 ], while others showed null [ 38 , 40 , 41 , 42 , 45 , 51 , 56 ] or negative effects [ 36 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference is that tDCS does not change polarity (i.e., is either positive or negative), whereas tACS rhythmically shifts polarity, which influences the depolarization and hyperpolarization states of the affected neurons. The studies of [ 33 , 37 ] suggested that the phase at which tACS is applied is crucial. Closed-loop transcranial alternating current stimulation (CL-tACS), a technique that involves using feedback from the brain to inform stimulation parameters without online human intervention, provides the most optimized method for delivering stimulation and entraining neurons in the human brain and has only recently been demonstrated [ 38 ].…”
Section: Introductionmentioning
confidence: 99%